â¤6-II Orbifold Model of the Heterotic String - Freddy Permana Zen; Bobby Eka Gunara; Asep Yoyo Wardaya (Institut Teknologi Bandung, 2005)
We study a â¤6-II orbifold model which is derived from the ten-dimensional SO(16) × SO(16) heterotic string theory whose the extra six dimensional space is devided by the â¤6-II rotations. All independent embeddings are classified using both shifting and rotation procedures of an SO(16) × SO(16) root lattice. SO(10) × SU(3) × U(1) × SO(16) models are elucidated as examples among the models.